Prevention of allergy by virus‐like nanoparticles (VNP) delivering shielded versions of major allergens in a humanized murine allergy model. Issue 2 (5th November 2018) - Kratzer, Bernhard; Köhler, Cordula; Hofer, Sandra; Smole, Ursula; Trapin, Doris; Iturri, Jagoba; Pum, Dietmar; Kienzl, Philip; Elbe‐Bürger, Adelheid; Gattinger, Pia; Mittermann, Irene; Linhart, Birgit; et al.
Abstract: Background: In high‐risk populations, allergen‐specific prophylaxis could protect from sensitization and subsequent development of allergic disease. However, such treatment might itself induce sensitization and allergies, thus requiring hypoallergenic vaccine formulations. We here characterized the preventive potential of virus‐like nanoparticles (VNP) expressing surface‐exposed or shielded allergens. Methods: Full‐length major mugwort pollen allergen Art v 1 was selectively targeted either to the surface or to the inner side of the lipid bilayer envelope of VNP. Upon biochemical and immunological analysis, their preventive potential was determined in a humanized mouse model of mugwort pollen allergy. Results: Virus‐like nanoparticles expressing shielded version of Art v 1, in contrast to those expressing surface‐exposed Art v 1, were hypoallergenic as they hardly induced degranulation of rat basophil leukemia cells sensitized with Art v 1‐specific mouse or human IgE. Both VNP versions induced proliferation and cytokine production of allergen‐specific T cells in vitro . Upon intranasal application in mice, VNP expressing surface‐exposed but not shielded allergen induced allergen‐specific antibodies, including IgE. Notably, preventive treatment with VNP expressing shielded allergen‐protected mice from subsequent sensitization with mugwort pollen extract. Protection was associated with a Th1/Treg‐dominated cytokine response, increased Foxp3 + Treg numbers in lungs, and reduced lung resistance when compared to mice treated with empty particles. Conclusion: Virus‐like nanoparticles represent a novel and versatile platform for the in vivo delivery of allergens to selectively target T cells and prevent allergies without inducing allergic reactions or allergic sensitization. Abstract : Allergen‐expressing VNP, which are produced in HEK 293T cells with the help of MoMLV structural proteins, are unable to stimulate allergen‐specific B cells or sensitized effector cells (basophils, mast cells). Instead, upon i.n. application, they are being taken up by lung‐resident CD103 + DC and alveolar macrophages, which unpack their (allergic) cargo, expand Foxp3 + Treg cells and prevent from sensitization.